Fenomena Maraknya Judi Online di Kalangan Masyarakat - Siregar, Dian Yustikartika Basri; Rosmalinda (PT. Meja Ilmiah Publikasi, 2025)
In our fast-paced and ever-evolving society, the accessibility of rights has reached unprecedented levels. Technological advances have changed the way individuals engage in various activities, facilitating access to a variety of beneficial and detrimental activities. Among the important impacts of these technological advances is the ease with which individuals can participate in unlawful activities, especially the shift from traditional gambling to online platforms. The practice of online gambling in our society does not have a strong legal basis, because it directly violates the Indonesian legal framework which strictly prohibits this activity. According to Article 27 paragraph (2) of the Information and Electronic Transactions Law (UU ITE), any person who intentionally and unlawfully disseminates, sends or provides information or electronic documents containing gambling content, is an unlawful act. Societal order is essentially closely intertwined with law, which functions as a crucial social control mechanism. This research aims to examine the sociology of law as a means of social regulation and to investigate the effectiveness of current law enforcement measures.